13 - Food Security in Epworth, Zimbabwe: Leveraging Rural-urban Linkages for Resilient Food Systems in Peri-urban Areas - Tawodzera, Godfrey (Africa Development, 2022)
In Zimbabwe, persistent political and economic problems have instigated and exacerbated food insecurity over the past two decades. Low food production, combined with high levels of inflation, a stagnating economy and increasing food prices, have worsened the plight of consumers in the country. High levels of poverty in the rural areas continue to influence rural-urban migrations, but most migrants to the city generally face deprivation, especially in peri-urban areas such as Epworth, where most migrants prefer to settle owing to its semi-formal nature. How then, do the poor in these peri-urban areas feed themselves amidst high urban poverty levels? Using data collected from different surveys between 2008 and 2016, the article explores four major strategies adopted by households to cope with food insecurity: reliance on urban farming; dependence on rural remittances; utilisation by urban residents of employment opportunities in the surrounding farms; and participation in, as well as dependence on, informality. A more nuanced appreciation of these survival strategies will engender an informed theoretical understanding on how to leverage these linkages to create resilient food systems in peri-urban areas.